2015
DOI: 10.1080/10494820.2015.1113709
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mobile devices in teaching: changes in teacher beliefs, attitudes and anxiety

Abstract: D. (in press). Adoption of mobile devices in teaching: changes in teacher beliefs, attitudes and anxiety. Interactive Learning Environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 34 publications
4
79
1
4
Order By: Relevance
“…Firstly, although this study the found that participation and performance are primarily predicted by viewing and to a lesser extent by commenting, more studies are needed to validate the finding. The results of the present study could also be extended by additional studies on other MOOCs in other subject domains (Chiu & Churchill, 2016). Secondly, this study did not consider another major learning activity -watching video lectures -and outcomes that are measured in different phases.…”
Section: Conclusion and Limitationsmentioning
confidence: 62%
“…Firstly, although this study the found that participation and performance are primarily predicted by viewing and to a lesser extent by commenting, more studies are needed to validate the finding. The results of the present study could also be extended by additional studies on other MOOCs in other subject domains (Chiu & Churchill, 2016). Secondly, this study did not consider another major learning activity -watching video lectures -and outcomes that are measured in different phases.…”
Section: Conclusion and Limitationsmentioning
confidence: 62%
“…Teachers' role can be catalytic in the acceptance of mobile learning and assessment (Chiu & Churchill, ). While previous studies have focused on teachers' acceptance of mobile learning (Mac Callum et al, 2014; Sánchez‐Prieto et al, ), the current study provides a step ahead towards the investigation of European STEM teachers' acceptance of mobile‐based assessment using individual, social, institutional and instruction design factors and proposes the TAMBA model.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the current study is that it focuses on STEM teachers. Previous research has shown that Science and Mathematics teachers, compared to Language and Humanities teachers, have more positive attitudes towards mobile devices (Chiu & Churchill, ). Therefore, generalization of the study findings to teacher groups with different backgrounds should be made with caution and future studies should include teachers with other backgrounds as well.…”
Section: Discussionmentioning
confidence: 99%
“…Creating opportunities for children to experience the richness of contemporary learning in the digital era and preparing children for future learning, teachers also learn to cope with various barriers that might be experienced in technology adoption, including changing beliefs and attitudes, and learning new skills in planning pedagogy aligned with teaching practices (Chiu & Churchill, 2016;Collier, Burkholder, & Branum, 2013).…”
Section: Change In Pedagogical Knowledgementioning
confidence: 99%
“…Other than external factors (support, technology, and environmental influences), internal factors (such as personal beliefs in the use of technology, capability in management, and perceived professional development) also influence teachers' adoption of technology in different school settings. Issues related to teachers' decisions regarding technology integration have been extensively discussed in prior studies (Blackwell, 2013;Chiu & Churchill, 2016;Hew & Brush, 2007;Liaw & Huang, 2015;Peterson, 2011;Phiri, Foko, & Mahwai, 2014;Polly & Orrill, 2016). These discussions underline the importance of teachers' attitudes, expectations, and facilitation conditions in the adoption process of tablet teaching.…”
mentioning
confidence: 99%